2018
DOI: 10.1093/ajcn/nqx059
|View full text |Cite
|
Sign up to set email alerts
|

The effects of apples and apple juice on acute plasma uric acid concentration: a randomized controlled trial

Abstract: The body acutely responds to fructose regardless of source. Longer-term studies are required to assess how small and transient increases in plasma uric acid contribute to health. This trial was registered with the Australian New Zealand Clinical Trials Registry at https://www.anzctr.org.au/trial/registration/trialreview.aspx?id=367974 as ACTRN12615000215527.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…One sugar in particular that has been associated with metabolic disturbance is fructose via its hepatic metabolism resulting in the production of uric acid [7]. Even the amount of fructose contained in one apple has been found sufficient to transiently raise postprandial uric acid concentration [57]. However, a diet high in fruit and vegetables is associated with relatively high urinary alkalinity [58] creating a physiological environment which predisposes to the elimination of uric acid from the body [59].…”
Section: Discussionmentioning
confidence: 99%
“…One sugar in particular that has been associated with metabolic disturbance is fructose via its hepatic metabolism resulting in the production of uric acid [7]. Even the amount of fructose contained in one apple has been found sufficient to transiently raise postprandial uric acid concentration [57]. However, a diet high in fruit and vegetables is associated with relatively high urinary alkalinity [58] creating a physiological environment which predisposes to the elimination of uric acid from the body [59].…”
Section: Discussionmentioning
confidence: 99%
“…It reported that after 30 minutes the fructose/glucose control increased SUA by 15 µmol/L (95% CI: 10, 21 µmol/L), apples increased SUA by 19 µmol/L (95% CI: 8, 30 µmol/L) and apple juice increased SUA by 17 µmol/L (95% CI: 9, 24 µmol/L). These increases were equivalent leading the authors to conclude that the SUA increases following ingestion of fructose, regardless of source [9].…”
Section: Table 10mentioning
confidence: 93%
“…After fructose ingestion, the acute increases in SUA are similar regardless of the source, i.e. whether the fructose is consumed in free form, fruit juice or fruit [9]. Yet, it appears that long-term consumption of foods containing fructose (NF), does not have the same cardiovascular and metabolic impact as fructose derived from artificial sweeteners (AF).…”
Section: Introductionmentioning
confidence: 99%
“…Sustained hyperuricaemia, which most commonly occurs secondary to reduced fractional uric acid clearance, is recognised as the most important risk factor for gout 9 10. Consumption of purine-rich or fructose-rich food and drink, including seafood, red meat, beer and sugar-sweetened beverages have been associated with increased uric acid levels and risk of gout flares 11–16…”
Section: Introductionmentioning
confidence: 99%
“…9 10 Consumption of purine-rich or fructose-rich food and drink, including seafood, red meat, beer and sugar-sweetened beverages have been associated with increased uric acid levels and risk of gout flares. [11][12][13][14][15][16] Early case reports from the 1950s suggested that consumption of cherries had a role to play in alleviating gouty pain and inflammation. 17 More recently, cherries and cherry products have been shown to acutely lower serum urate after consumption in healthy people, while a daily supplement of cherry juice was associated with lower serum urate in Open access a placebo-controlled cross-over study of men and women who are overweight or have obesity.…”
Section: Introductionmentioning
confidence: 99%